Strength of soft clay reinforced with single crushed polypropylene (pp) column - Noor Amirah, Noor Shahrudeen (2015)
The strength of the kaolin clay increases when being reinforced with a material that are stronger than itself. The reason for conducting this study is to solve certain problem that related to the bearing capacity of the soft clay on the ground. Besides of throwing out an excessive amount of uncycled material, this study proposed to save an environment by re-use the excessive material to strengthen up the soft clay. There is two objective of this study that need to be completed by the end of the research. The first one is to determine the physical characteristics of kaolin clay and PP and morphological characteristic of PP. The second objective is to determine the undrained shear strength of soft clay reinforced with various dimensions of single PP column. Generally, soft clays can be defined as a disturbed cohesive soil that its water content is higher than its liquid limit. Soft clay also is one of the fine grained soils types that experiences the change in volume when it is different from elastic deformation, consolidation and secondary compression. Rock that rich in kaolinite are known as kaolin or china clay. Kaolin or china clay is a hydrated aluminium silicate crystalline mineral (kaolinite) formed over many millions of years by the hydrothermal decomposition of granite rocks. Kaolin clay is a versatile industrial mineral and generally used as fillers or raw material in ceramic, paints, plastics, paper, rubber, ink, catalyst, insecticide, pharmaceutical formulation and etc. Kaolin clay was familiarly experience with a various type of soil failure because of its characteristics due to the weak in strength. The failure that frequently happened to this kind of soil was the settlement failure. It is because the soil can’t resist the large amount of loads through the member of the structure. Many improvement of soft clay has been discovered in order to make the strength of the kaolin clay rise. Meanwhile, Polypropylene (PP) are the general class of thermoplastics produced from propylene gas. Propylene gas is derived from the cracking of natural gas or petroleum by-products. The symbol for this polymer was (C3H6)n. Production of PP takes place by slurry, solution or gas phase process, in which the propylene monomer is subjected to heat and pressure in the presence of a catalyst system. Polymerisation is achieved at relatively low temperature and pressure and the product yielded is translucent, but readily coloured. Differences in catalyst and production conditions can be used to alter the properties of the plastic. As for the testing, there is six (6) basic tests that need to be conducted towards the kaolin clay and two (2) basic tests for PP. The UCT will be proceed after all the basics test of the material has been done. A total of 28 sample need to be tested using the UCT. Four of the 28 sample was taken out to be the controlled sample. The other 24 samples with the PP column are tested and the results was compared to the controlled sample. If the results of the 24 samples showing an improvement of soil strength, the experiment was considered successful.